Proses Evaluasi Pembelajaran Pendidikan Jasmani, Olahraga, dan Kesehatan SD Negeri di Kecamatan Kertek Kabupaten Wonosobo - Saputro, Andi; Raharjo, Hermawan Pamot (Indonesian Journal for Physical Education and Sport, 2023)
The research problem is the process of evaluating learning PJOK for public elementary schools has not been identified in Kertek District. The purpose of this study was to determine the implementation of the evaluation process of attitudes, knowledge, and skills of public elementary schools in Kertek District, Wonosobo Regency. The method used is descriptive method with a quantitative approach. The results of the study of 24 physical education teachers at the State Elementary School in Kertek District found that the attitude assessment process was 83.33% (20 teachers) in the very good category, 16.67% (4 teachers) in the good category, then the knowledge assessment process was 29.17% ( 7 teachers) in the very good category, 70.83% (17 teachers) in the good category and the skills assessment process there were 8% (2 teachers) in the very good category, 87.5% (21 teachers) in the good category, 4, 17% (1 teacher) in the sufficient category. The conclusion is that the evaluation process for learning PJOK in SD Negeri in Kertek District which includes the attitude assessment process, knowledge assessment, and skills assessment as a whole can be said to have been carried out well because seen from the results the average teacher is in the good category, namely the interval of 62.49%- 81.24%.